Gendered Communication in Red Dead Redemption 2 - Syafiq, Alif Muhammad; EF, Abd Hannan; Wardoyo, Cipto (Universitas Pahlawan Tuanku Tambusai, 2025)
The role of language in shaping social identity is prominent, especially in the representation of gender in digital narratives. This study investigates language choices in Red Dead Redemption 2 through Deborah Tannen's genderlect theory, which focuses on rapport talk (female language style characterized by relationality and expressivity), and report talk (male language style that emphasizes status, information, and dominance). Using descriptive qualitative methods, this study shows that female characters mostly display rapport talk and report talk is mostly displayed by male characters. However, some characters portray a combination of both, adding to the complexity of gender presentation in digital media. The results show how video games can reinforce or reaffirm linguistic representations of gender stereotypes.